The securities market and underdevelopment : the stock exchange in the Ivory Coast, Morocco, Tunisia - Calamanti, Andrea (Milan : Finafrica : Giuffrè, 1983)
This reappraisal is mainly intended to supply conceptual terms of reference for the subsequent analysis of stock markets in French-speaking African countries, and is based on setting the arguments put forward in the most significant existing theoretic studies in perspective against what can be learned in practice from the actual experience of the countries investigated in the survey
Translation of: Mercato mobiliare e sottosviluppo.
Includes indexes.
Bibliography: p. [209]-215.
osc 24/07/2018
Loans
Keywords: Stock exchanges; Stock exchanges; Stock exchanges